Mouse Models in Sarcopenia Research: A Literature Review - Julia, Putri; Nani Asyahri; Fitriya Setiani; Lili Sardona; Jodion Siburian; Afreni Hamidah; Desfaur Natalia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Sarcopenia is defined as the progressive decline in skeletal muscle mass, strength, and function associated with the aging process. This literature review aims to analyze various mouse models used in sarcopenia research, with a primary focus on the C57BL/6 strain. A narrative literature review was conducted systematically by searching the Scopus and Google Scholar databases using the keywords “sarcopenia”, “mouse model”, “muscle atrophy”, and “C57BL/6”. A total of 12 relevant articles published between 2020 and 2024 were selected based on the inclusion criteria.The analysis results showed that muscle mass decline in mice generally begins progressively at the age of 18–24 months and becomes more significant at 23-32 months, with male mice being more susceptible than females. Natural aging, dexamethasone induction, and immobilization models were the most frequently used, consistently demonstrating type II fiber atrophy, mitochondrial dysfunction, increased ROS, and suppression of the mTORC1 pathway. Therapeutic candidates such as Delta-Like 1 Homolog (DLK1) and Ulmus macrocarpa extract showed promising effects in reducing muscle atrophy. Although mouse models provide valuable insights into the mechanisms of sarcopenia, biomechanical differences and sex-specific responses between mice and humans must be considered to enhance the translational value of the research. This review is expected to serve as a reference for researchers in selecting the appropriate mouse model for sarcopenia studies.